Avaliação das atividades genotóxica e antigenotóxica do extrato etanólico de Lafoensia pacari A. St-Hil em bactérias e camundongos - Lima, Débora Cristina da Silva (2012)
Lafoensia pacari A. St. Hil. (Lythraceae), popularly known in Brazil as “pacari”, is a species native of Cerrado. In folk medicine, the leaves and stem bark are used to treat cancer and as an anti-inflammatory and cicatrizant agent. Due to the wide use of this plant as a therapeutic resource, the present study evaluated the genotoxic, cytotoxic, antigenotoxic, and anticytotoxic activities of the ethanolic extract from L. pacari stem bark and leaves using the Ames test and the mouse bone marrow micronucleus test. Our results demonstrated that the ethanolic extract from L. pacari leaves, presented no mutagenic activity in bacteria, but presented a mild genotoxicity in the highest concentration at 24 h in mice bone marrow cells. Exhibited moderate cytotoxic effect on bacteria and a mild cytotoxic action in the highest concentration by micronucleus test. The extract showed antimutagenic activity by Ames test and in the micronucleus test demonstrated antigenotoxic action in all concentrations at 24 h, and in the lowest concentration at 48 h. Showed anticytotoxic effect in all concentrations and times tested. In the evaluation of the genotoxic, cytotoxic, antigenotoxic and anticytotoxic activities of the ethanolic extract from L. pacari stem bark, the results demonstrated that the extract exhibited no mutagenic activity in bacteria, however showed a mild genotoxicity in the highest concentration in mice. Exhibited moderate cytotoxic effect in bacteria and a mild cytotoxicity at 24 h by micronucleus test. Showed strong antimutagenic activity by Ames test, as well as antigenotoxic and anticytotoxic activities in the mouse bone marrow micronucleus test, demonstrating to be a strong protective agent against DNA damage.